A Case Report of Implant Fracture of Extensively Porous-Coated, Distally Fixated Cementless Long Stem: Detailed Course of Stem Bending Development - Tomohiro Mimura (Case Reports in Orthopedics)
We report the fracture of a cementless long stem in a distally fixated, extensively porous-coated femoral prosthesis used for revisional total hip arthroplasty (THA) 9 years previously in a 48-year-old woman, measuring 58 kg in weight and 155 cm in height. Following resolution of an infection 7 years after the revisional THA, a series of posterior dislocations occurred up until 7 months before sudden stem fracture. Extensive radiographic imaging evidence indicated a gradual progression of bending in the stem, and scanning electron microscope energy dispersive X-ray spectroscopy revealed oxygen in the medial and lateral sections, suspecting in vivo corrosion. We retrospectively examined the detailed course of stem bending development prior to stem fracture. The stem bending immediately after the revisional THA, at the first dislocation, and immediately before the stem fracture was 0°, 1.9°, and 5.2°, respectively. We consider that the cyclic loading with poor proximal bone support, distal fixation, and small diameter were the potential risk of this implant fracture. However, the course of stem bending development suggested that repeated operations and several dislocations might have aggravated the implant fatigue in the present case.